Features of ecological discourse in the policy of the Latin American states - A. A. Shinkarenko (Ибероамериканские тетради)
At the beginning of XXI century, there was a tendency towards the active implementation of the neoextractive paradigm in the economy of Latin American states, which was due to the existing“consensus of the commodities”. This term is interpreted by researchers as an economic, political and ideological order, which is based on the high demand for commodities in international markets. Despite impressive successes in filling up national reserves with funds received from the extractive industries, new forms of inequality and potential conflicts began to arise in Latin American society. The costs of the current model predetermined not only appeal to environmental discourse, but also to increasing of its supporters that allows them to outline their demands on the political landscape.